Synthesis of substituted pyridines from 1,2-nucleophilic addition products of functionalized N-acy1-2,3-dihydropyridones - Güzel, Mustafa; Watts, Joshua; McGilvary, Matthew; Wright, Marcus; Kiren, Sezgin (Pergamon-Elsevier Science, 2015)
We describe herein a general and efficient synthetic approach toward substituted pyridines from functionalized N-acy1-2,3-dihydropyridones in two steps; 1,2-addition with organocerium reagents and subsequent oxidative aromatization with chloranil. This strategy allows the generation of pyridines with various substitution patterns and introduces a variety of substituents including aryl, alkyl, alkynyl, alkenyl, and heteroaryl groups at the desired positions.
WOS: 000360510700004
Keywords: Substituted Pyridines; N-Acyl-2,3-Dihydropyridones; Oxidative Aromatization; Chloranil; 1,2-Nucleophilic Addition